19. CHANGING SELF-CARE KNOWLEDGE OF URINARY FIBROSURGERY PATIENTS AFTER HEALTH EDUCATION INTERVENTION AT NAM DINH PROVINCE HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the current status of self-care knowledge of patients undergoing urolithiasis and evaluate their knowledge change after health education interventions at Nam Dinh Provincial General Hospital in 2024.Method: Patients after surgery for urolithiasis were treated at the Department of Nephrology - Urology, Ninh Binh Provincial General Hospital. Research period: From 6/2024 to the end of 12/2024. Study subjects: 314 patients. Educational intervention study with comparison before and after at 3 time points T1: The first assessment was conducted right after the patient was hospitalized for treatment. T2: The second assessment immediately after the patient received educational intervention (After the first assessment one day). T3: The third assessment was conducted 1 month after the educational intervention (1 month ± 10 days).Results: Patients undergoing urinary system stone surgery had pre-intervention self-care knowledge at a satisfactory level of 54% and an unsatisfactory level of 46%. After 1 day of intervention, the rate of self-care knowledge was at a satisfactory level of 86%. After 1 month, the proportion of study subjects with satisfactory self-care knowledge was 82%. This difference is statistically significant with p < 0.001.Conclusion: Self-care knowledge of patients with urinary system stone surgery before intervention is still low. There is a marked change in self-care knowledge of patients undergoing urolithiasis surgery one month after the intervention.
Keywords: Urinary stones; Self-care after urinary stone surgery.